BIODIVERSITY ASSESSMENT AND REINTRODUCTION – BASED CONSERVATION OF FRESHWATWER FISHES IN THE ANCIENT RIVER, BELITUNG ISLAND, INDONESIA - Valen, Fitri Sil; Samsuddin, M. Afdal; Syarif, Ahmad Fahrul; Hafidz, Agus Miftahudin; Althaaf, Yafsar Murfid; Kusumah, Wanda; Yusnandar, Firman; Wijaya, Imam (Journal of Aquatropica Asia, 2025)
Freshwater fish biodiversity in Belitung Island has undergone a significant decline due to extensive tin mining activities and the rapid expansion of oil palm plantations. In response to these ecological pressures, a biodiversity assessment was conducted in 2024 in the Lenggang River system—an ancient freshwater ecosystem located in East Belitung, Indonesia. The primary aim was to document native and endemic fish species and to establish a reintroduction-based conservation strategy tailored to the river's ecological context. Field surveys recorded high ichthyofaunal diversity, from which 32 native species were selected for reintroduction based on ecological value, conservation status, endemism, and their capacity to adapt to rehabilitated habitats. Among the prioritized taxa was Gymnochanda verae, a rare and endemic species found exclusively in the Bangka–Belitung region. Other selected species include Gymnochanda verae, Desmopuntius gemellus, Osteochilus spilurus, Osteochilus flavicauda, Eirmotus insignis, Brevibora cheeyai and Aplocheilus armatus. The reintroduction initiative was designed not only to restore declining populations but also to enrich the genetic diversity of native fish communities. Importantly, all reintroduced species were confirmed to be historically present and indigenous to the Lenggang River system. The conservation strategy was further supported by habitat restoration, local community involvement, and long-term population monitoring. Preliminary results indicate positive acclimatization in restored zones, underscoring the potential of species reintroduction as an effective tool for freshwater biodiversity conservation in ancient tropical river systems. This study provides essential baseline data and offers a replicable model for integrated conservation of freshwater ecosystems in Southeast Asia.